Intra-Asia Exchange Rate Volatility and Intra-Asia Trade: Evidence by Type of Goods - Hsiao Chink Tang (Asian Development Bank (ADB), 2011)
This paper examines the impact of intra-Asia exchange rate volatility on intra-Asia trade in primary goods, intermediate goods, equipment goods, and consumption goods from 1980 to 2009. For Asia, the evidence shows that as intraregional exchange rate volatility increases, intraregional exports in these goods fall. This adverse impact is even more pronounced in the sub-region of Association of Southeast Asian Nations (ASEAN)+5 comprising ASEAN member countries plus the People's Republic of China; Hong Kong, China; Japan; the Republic of Korea; and Taipei,China; and especially among intermediate and equipment exports. Again, the impact magnifies in an even smaller sub-group excluding the smaller ASEAN economies. These results underline the significant impact of exchange rate volatility on the region's production networks. For South Asia, however, exchange rate volatility appears to have a positive impact on exports. Still, caution is warranted given that South Asian economies trade relatively little with each other.
hdl:11540/1987
Keywords: F10; F14; F31; 330; exchange rate volatility; trade; ASEAN; East Asia